see the attached figure to better understand the problem
Step ![1](https://tex.z-dn.net/?f=1)
<u>Find the area of the parallelogram
</u>
Find the area of the complete square and subtract the area of the four triangles
so
<u>Area of the complete square</u>
![A=6^{2}=36\ unit^{2}](https://tex.z-dn.net/?f=A%3D6%5E%7B2%7D%3D36%5C%20unit%5E%7B2%7D)
<u>Area of the four triangles</u>
![A=4*[\frac{1}{2}*2*4]=16\ unit^{2}](https://tex.z-dn.net/?f=A%3D4%2A%5B%5Cfrac%7B1%7D%7B2%7D%2A2%2A4%5D%3D16%5C%20unit%5E%7B2%7D)
<u>Area of the parallelogram
</u>
![A1=36\ unit^{2}-16\ unit^{2}=20\ unit^{2}](https://tex.z-dn.net/?f=A1%3D36%5C%20unit%5E%7B2%7D-16%5C%20unit%5E%7B2%7D%3D20%5C%20unit%5E%7B2%7D)
Step ![2](https://tex.z-dn.net/?f=2)
<u>Find the area of the parallelogram
</u>
Find the area of the complete rectangle and subtract the area of the four triangles
so
<u>Area of the complete rectangle</u>
![A=4*8=32\ unit^{2}](https://tex.z-dn.net/?f=A%3D4%2A8%3D32%5C%20unit%5E%7B2%7D)
<u>Area of the four triangles</u>
![A=2*[\frac{1}{2}*2*6]+2*[\frac{1}{2}*2*2]=16\ unit^{2}](https://tex.z-dn.net/?f=A%3D2%2A%5B%5Cfrac%7B1%7D%7B2%7D%2A2%2A6%5D%2B2%2A%5B%5Cfrac%7B1%7D%7B2%7D%2A2%2A2%5D%3D16%5C%20unit%5E%7B2%7D)
<u>Area of the parallelogram
</u>
![A2=32\ unit^{2}-16\ unit^{2}=16\ unit^{2}](https://tex.z-dn.net/?f=A2%3D32%5C%20unit%5E%7B2%7D-16%5C%20unit%5E%7B2%7D%3D16%5C%20unit%5E%7B2%7D)
Step ![3](https://tex.z-dn.net/?f=3)
<u>Compare the areas</u>
![A1=20\ unit^{2}](https://tex.z-dn.net/?f=A1%3D20%5C%20unit%5E%7B2%7D)
![A2=16\ unit^{2}](https://tex.z-dn.net/?f=A2%3D16%5C%20unit%5E%7B2%7D)
![A1-A2=20-16=4\ unit^{2}](https://tex.z-dn.net/?f=A1-A2%3D20-16%3D4%5C%20unit%5E%7B2%7D)
![A1=A2+4\ unit^{2}](https://tex.z-dn.net/?f=A1%3DA2%2B4%5C%20unit%5E%7B2%7D)
therefore
<u>the answer is the option </u>
The area of parallelogram 1 is 4 square units greater than the area of parallelogram 2.